A Critical Review on Floating Drug Delivery and Hydrodynamic Balanced Systems - Manoj Kumar Goyal; Ashutosh Dubey (Current Research in Pharmaceutical Sciences, 2016)
Drugs with narrow absorption window in the gastrointestinal tract have poor absorption. Therefore, hydrodynamically balanced systems (HBS) have been developed, which prolong the gastric emptying time. Several techniques such as floating drug delivery system, low density systems, raft systems, mucoadhesive systems, high density systems, superporous hydrogels and magnetic systems, have been employed. Floating drug delivery systems have a bulk density less than gastric fluids and so, remain buoyant in the stomach for a prolonged period of time, releasing the drug slowly at the desired rate from the system. Dosage forms available as gastric floating systems include tablets, capsules, granules and microspheres. This review on GRDDS attempts to compile the available information with all the possible mechanisms used to achieve gastric retention.